Detection of the Information Leakage Channel from Multimode Optical Fiber Using a Silicone Photomultiplier - I. R. Gulakov; A. O. Zenevich; O. V. Kochergina; T. A. Matkovskaia (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
Currently, fiber-optic communication lines are widely used for data transmission. Despite the fact that the information signal propagates inside the optical fiber, covered with a protective shell, there are various ways to form information leakage channels from such fibers. The power control of the information signals transmitted over an optical fiber is one of the most common ways to detect an information leakage channel. This paper determines the parameters of a fiber-optic communication line based on multimode optical fibers for which silicon photomultipliers to detect information leakage channels can be used. The dependences of the branched power on the fiber bending diameter are presented. It has been found that the bending diameter increase leads to the branched power decrease and a decrease in the ability of the photodetector to detect power loss in the optical fiber. The value of the branched power of optical radiation with a wavelength of 850 nm is greater than for 650 nm for all studied bending diameters. It has been established that an increase in the optical radiation power introduced into the fiber to 10 mW makes it possible to detect power loss up to –0.005 dB for an optical radiation wavelength of 850 nm, and –0.142 dB for a wavelength of 650 nm. The results of this article can be used in systems for protecting information transmitted over fiber-optic communication lines.